Identity and relationship-based discrimination, and mental health in a sample of sexual minority male couples. Issue 1 (2nd January 2022) - Robles, Gabriel; Dellucci, Trey V.; Gupta, Sugandha K.; Rosenthal, Lisa; Starks, Tyrel J.
Abstract: Purpose: The study explored the unique associations of individual identity-based discrimination and relationship-based discrimination with mental health among sexual minority male couples. It also examined whether couples' relationship functioning moderated associations between relationship-based discrimination, the experience of one's romantic relationship being devalued, and mental health outcomes. Methods: Baseline dyadic data drawn from a clinical trial involving 70 couples (N = 140) were analyzed using Actor-Partner Interdependence Modeling. The sample consisted of sexual minority men, of which 54.3% identified as a person of color. Each partner completed the computerized survey independently. Data were collected using the Relationship Marginalization Scale, Dyadic Adjustment Scale, Generalized Anxiety Disorder-7, and Center for Epidemiologic Studies Depression Scale-Revised scales. Results: Dyadic adjustment moderated (i.e., buffered against) the association between relationship-based discrimination and depressive symptoms. The effects appeared to follow an intra-individual pattern ( BACTOR = −0.06, p = .048 and BPARTNER = −0.07, p = .030). The interaction terms predicting anxiety yielded non-significant results. Conclusions: The current research suggests that dyadic functioning buffers against the effects of stigma. These findings point to the potential utility of interventions to improve relationship functioning into interventions addressing stigma among partnered sexual minority men.